Respiratory Effects of the Atypical Tricyclic Antidepressant Tianeptine in Human Models of Opioid-induced Respiratory Depression. (22nd July 2022) - Algera, Hyke; van der Schrier, Rutger; Cavalla, David; van Velzen, Monique; Roozekrans, Margot; McMorn, Alison; Snape, Michael; Horrigan, Joseph P.; Evans, Stuart; Kiernan, Bernard; Sarton, Elise; Olofsen, Erik; et al.
Abstract : Background: Animal data suggest that the antidepressant and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor modulator tianeptine is able to prevent opioid-induced respiratory depression. The hypothesis was that oral or intravenous tianeptine can effectively prevent or counteract opioid-induced respiratory depression in humans. Methods: Healthy male and female volunteers participated in two studies that had a randomized, double blind, placebo-controlled, crossover design. First, oral tianeptine (37.5-, 50-, and 100-mg doses with 8 subjects) pretreatment followed by induction of alfentanil-induced respiratory depression (alfentanil target concentration, 100 ng/ml) was tested. Primary endpoint was ventilation at an extrapolated end-tidal carbon dioxide concentration of 55 mmHg (V̇E 55). Next, the ability of four subsequent and increasing infusions of intravenous tianeptine (target tianeptine plasma concentrations 400, 1, 000, 1, 500, and 2, 000 ng/ml, each given over 15 min) to counteract remifentanil-induced respiratory depression was determined in 15 volunteers. Ventilation was measured at isohypercpania (baseline ventilation 20 ± 2 l/min). The primary endpoint was minute ventilation during the 60 min of tianeptine versus placebo infusion. Results: Alfentanil reduced V̇E 55 to 13.7 (95% CI, 8.6 to 18.8) l/min after placebo pretreatment and to 17.9 (10.2 to 25.7) l/min after 50-mg tianeptine pretreatment (mean difference between treatments 4.2 (–11.5 to 3.0) l/min, P = 0.070). Intravenous tianeptine in the measured concentration range of 500 to 2, 000 ng/ml did not stimulate ventilation but instead worsened remifentanil-induced respiratory depression: tianeptine, 9.6 ± 0.8 l/min versus placebo 15.0 ± 0.9 l/min; mean difference, 5.3 l/min; 95% CI, 2.5 to 8.2 l/min; P = 0.001, after 1 h of treatment. Conclusions: Neither oral nor intravenous tianeptine were respiratory stimulants. Intravenous tianeptine over the concentration range of 500 to 2000 ng/ml worsened respiratory depression induced by remifentanil. Abstract : The hypothesis that tianeptine is able to cause effective reversal of opioid-induced respiratory depression was tested in 15 male and female subjects in a double-blind, randomized, placebo-controlled crossover study by determining the effect of tianeptine at four increasing target plasma concentrations on remifentanil-induced respiratory depression at isohypercapnia. Over the plasma tianeptine concentration range tested (500 to 2, 000 ng/ml), it did not produce respiratory stimulation during remifentanil-induced respiratory depression but instead worsened respiratory depression with a further decline in ventilation at an extrapolated end-tidal carbon dioxide concentration of 55 mmHg by 5 l/min.